(untitled) (Modern education and development, 2025)
This article is about the life and works of one of the People’s poets of Uzbekistan Muhammmad Yusuf. Our data are taken from some books of the poet and web sites. The piece of the epic is translated into English by the authors of the article. There are also mentioned the names of the poet’s works in Uzbek language in order to be clear.